Determinantes del éxito en los emprendimientos registrados en el municipio de Riobamba periodo 2017-2019 - Jessica Elizabeth, Cáceres Guzmán (2021)
and trade experience are signicant with a percentage of less than 5%. However, the variable family entrepreneurs was included in the model with a significance value of less than 10%. Keywords: Determinants, entrepreneurship, success, binomial logistic regression. Reviewed by: MsC. Adriana Cundar, PhD. ENGLISH PROFESSOR c.c. 1709268534